[OP.6C.04] PREDICTORS OF DRUG NON-ADHERENCE IN OUT-PATIENTS OF A UNIVERSITY HOSPITAL: URINARY DRUG DETECTION VS. MORISKY 4-ITEMS QUESTIONNAIRE. (September 2016) - Hamdidouche, I.; Jullien, V.; Boutouyrie, P.; Billaud, E.; Azizi, M.; Laurent, S.
Abstract : Objective: Suboptimal drug adherence may prove to be the greatest barrier to the effectiveness of antihypertensive agents (AHT). Thanks to LC-MS/MS technology, urinary drug detection (UDD) may represent an important advancement to monitor non-adherence in routine clinical practice. Our aim was to assess drug adherence by UDD and compare it to the 4-item Morisky Medication Adherence Scale (MMAS-4). Design and method: 169 patients (68 ± 11 yrs, 58 % women) with primary hypertension followed in the out-patient clinic of a university hospital were included. They received a median of 2 AHT (range 1–4) and most had controlled office BP. MMAS-4 was filled out and urine sampling was performed immediately after oscillometric BP measurement by a nurse and before the visit with the physician. Adherence to prescribed AHT was assessed by LC-MS/MS detection in the urine sample. UDD non-adherence was defined as presence of undetected urine levels of at least one prescribed AHT. Patients were not aware of the measurement. MMAS-4 non-adherence was defined as a score > 0. UDD was taken as a reference. Results: UDD full adherence (detection of all AHT) was observed in 157 patients (67 ± 11 yrs, 131 ± 14/ 72 ± 9 mmHg), and non-adherence in 12 patients (7%) only (73 ± 7 yrs, 144 ± 18/74 ± 13 mmHg; p = 0.01 vs full-adherence). MMAS-4 non adherence was observed in 16% patients. Compared to UDD used as a reference, MMAS-4 had a sensitivity of 84.7% and a specificity of 16.7%. A weak agreement was found between UDD and MMAS-4, with 33/162 non concordant tests. In multivariate analysis, the determinants of UDD non-adherence were office SBP (OR 0.95, IC [0.91- 0.99] per 1 mmHg, p = 0.04, ) and diuretic + beta-blocker combination (OR 0.1, IC [0.01 – 0.88], p = 0.03) but not MMAS-4. In multivariate analysis, the only determinant of MMAS-4 non-adherence was age (OR 1.04, IC [1.01–1.08], p = 0.02). Conclusions: In conclusion, the Morisky-4 items questionnaire proved a limited effectiveness in detecting non-adherent patients. Objective measurement of non-adherence, such as urinary detection of AHT, is applicable to clinical practice, providing that LCMS/MS technique is available in the clinical center. Multivariate analyses showed that UDD captured the classical predictors of non-adherence.